Cost effectiveness and clinical efficacy of patent foramen ovale closure as compared to medical therapy in cryptogenic stroke patients: A detailed cost analysis and meta-analysis of randomized controlled trials. (15th December 2018) - Pickett, Christopher A.; Villines, Todd C.; Resar, Jon R.; Hulten, Edward A.
Abstract: Background: Up to half the patients with cryptogenic stroke under the age of 55 years have been found to have a PFO. Observational studies have demonstrated a benefit from closure of PFO and several RCTs have shown a trend toward benefit. The cost and clinical effectiveness of PFO closure is unclear. Methods and results: We searched for RCTs of PFO closure in patients with cryptogenic stroke and performed a detailed cost analysis and meta-analysis of treatment outcomes based on the results of the meta-analysis. Five RCTs containing 3404 patients with cryptogenic stroke were included. Of these 1829 underwent PFO closure and 1611 received medical therapy. Mean follow-up was 4.0 years. PFO closure achieved cost effectiveness (<$50, 000/Quality-adjusted life-year gained) 2.7 years (95% Confidence Interval (CI) 2.2–3.4) after closure. The incremental cost to prevent one combined end point (CEP, combined transient ischemic attack (TIA), stroke, and death) by PFO closure was $535, 655(95% CI $458, 329–$642, 674). After 55.4 years (95%CI 51.1–60.5) of follow-up, the per patient total cost of medical therapy exceeded that of PFO closure. PFO closure demonstrated clinical efficacy with a decreased risk of CEP (pooled hazard ratio (HR = 0.43(95%CI 0.27–0.59))) and a decreased risk of stroke (HR = 0.29(95%CI 0.02–0.57)). Conclusions: In comparison to medical therapy alone, PFO closure appears to be cost-effective and clinically efficacious. Highlights: The cost and clinical effectiveness of patent foramen ovale (PFO) closure in cryptogenic stroke is unclear. This detailed cost analysis of five randomized controlled trials (RCT) of PFO closure shows PFO closure to achieve cost effectiveness (<$50, 000/Quality-adjusted life-year gained) 2.7 years after closure. This meta-analysis of five RCTs demonstrates the clinical efficacy PFO closure with decreased risk of stroke and combined transient ischemic attack, stroke and death. PFO closure appears to be cost-effective and clinically efficacious.